Spell it right dictionary - Maxwell, Christine (Berlitz, 2007)
From Berlitz, the Spell It Right Dictionary will help businesspeople, writers and students - native and non-native speakers of English alike - spell correctly. Includes: extensive misspellings, easy to use color coded word lists, proper spellings in proper context, i.e. Hi (to call attention) vs. high (tall)